Neonatal diarrhea in piglets associated with cpb-2 positive Clostridium perfringens - Silva , Rodrigo O. S.; Lobato , Francisco C. F.; Pires , Prhiscylla S.; Gabardo , Michelle P.; Paladino , Eliana S.; Guedes, Roberto M. C. (Brazilian Journal of Veterinary Pathology, 2013)
Clostridium perfringens type A (CPA) has been recognized as one of the most important cause of neonatal diarrhea in piglets. Despite its importance, the pathogenesis of CPA-associated disease is still unclear and data regarding its occurrence in Brazil is scarce. In light of this, the aim of this study was to report a case of neonatal diarrhea in piglets by CPA encoding beta-2 toxin gene (cpb-2). Three three-day-old piglets from a 2000-sow herd with history of diarrhea were necropsied and intestinal samples were collected for histology, immunohistochemistry, and feces samples were collected for bacteriologic and molecular procedures. Gross and histopathology revealed superficial necrotic enteritis associated with colonies of bacilli adhered to the exposed lamina propria. These ileal and jejunum fragments were positive for C. perfringens by immunohistochemistry, while anaerobic colonies were identified by PCR multiplex as CPA with the cpb-2. No other enteropathogen was identified from intestinal samples. The C. perfringens isolated strains were susceptible to penicillin, metronidazole and vancomicyn and resistant to eritromycin, enrofloxacin, oxitetracyclin and lincomycin.